Single Molecules and Nanotechnology - Rigler, Rudolf; Vogel, H. (Springer Series in Biophysics, 2008)
This book focuses on recent advances in the rapidly evolving field of single molecule research. These advances are of importance for the investigation of biopolymers and cellular biochemical reactions, and are essential to the development of quantitative biology. Written by leading experts in the field, the articles cover a broad range of topics, including: quantum photonics of organic dyes and inorganic nanoparticles their use in detecting properties of single molecules the monitoring of single molecule (enzymatic) reactions single protein (un)folding in nanometer-sized confined volumes the dynamics of molecular interactions in biological cells The book is written for advanced students and scientists who wish to survey the concepts, techniques and results of single molecule research and assess them for their own scientific activities.